Pengaruh Adopsi Teknologi, Ekspektasi Keuntungan, Lingkungan Sosial, dan Motivasi Bisnis Islami terhadap Keberhasilan UMKM Sektor Fashion - Rizky Amelia Siregar; Rahmat Daim Harahap; Juliana Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The achievement of Micro, Small, and Medium Enterprises (MSMEs) depends on multiple elements, such as the integration of technology, anticipated profits, surrounding social conditions, and Islamic-based business drivers. This research investigates how these four aspects impact the performance of fashion MSMEs located in Olympia Plaza, Medan. Utilizing a quantitative associative method, the study involved a total population of 121 business owners. A saturated sampling method was applied, meaning all 121 individuals were included as respondents. Information was gathered via questionnaires and processed using multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. The results reveal that integrating technology and expecting profits individually bring a positive and meaningful impact on business success. On the other hand, social surroundings and Islamic business drivers do not show a significant partial effect. When combined, however, all four elements significantly drive MSME success, yielding an Adjusted R² of 0.944. Ultimately, this highlights that maximizing tech usage and building strong profit outlooks are the most crucial steps to boost MSME performance.